Blood Pressure Targets in Subjects With Type 2 Diabetes Mellitus/Impaired Fasting Glucose: Observations From Traditional and Bayesian Random-Effects Meta-Analyses of Randomized Trials - Bangalore, Sripal; Kumar, Sunil; Lobach, Iryna; Messerli, Franz H. (Circulation (New York, N.Y.), 2011)
Most guidelines for treatment of hypertension recommend a blood pressure (BP) goal of <140/90 mm Hg, and a more aggressive goal of <130/80 mm Hg for patients with diabetes mellitus. However, in the recent Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial, a lower BP was not beneficial. The optimal BP target in subjects with diabetes mellitus or those with impaired fasting glucose/glucose tolerance is therefore not well defined. We performed PUBMED, EMBASE, and CENTRAL searches for randomized clinical trials from 1965 through October 2010 of antihypertensive therapy in patients with type 2 diabetes mellitus or impaired fasting glucose/impaired glucose tolerance that enrolled at least 100 patients with achieved systolic BP of ≤ 135 mm Hg in the intensive BP control group and ≤ 140 mm Hg in the standard BP control group, had a follow-up of at least 1 year, and evaluated macrovascular or microvascular events. We identified 13 randomized clinical trials enrolling 37 736 participants. Intensive BP control was associated with a 10% reduction in all-cause mortality (odds ratio, 0.90; 95% confidence interval, 0.83 to 0.98), a 17% reduction in stroke, and a 20% increase in serious adverse effects, but with similar outcomes for other macrovascular and microvascular (cardiac, renal, and retinal) events compared with standard BP control. The results were similar in a sensitivity analysis using a bayesian random-effects model. More intensive BP control (≤ 130 mm Hg) was associated with a greater reduction in stroke, but did not reduce other events. Meta-regression analysis showed continued risk reduction for stroke to a systolic BP of <120 mm Hg. However, at levels <130 mm Hg, there was a 40% increase in serious adverse events with no benefit for other outcomes. The present body of evidence suggests that in patients with type 2 diabetes mellitus/impaired fasting glucose/impaired glucose tolerance, a systolic BP treatment goal of 130 to 135 mm Hg is acceptable. However, with more aggressive goals (<130 mm Hg), we observed target organ heterogeneity in that the risk of stroke continued to fall, but there was no benefit regarding the risk of other macrovascular or microvascular (cardiac, renal and retinal) events, and the risk of serious adverse events even increased.